ENHANCING PROFESSIONAL DEVELOPMENT THROUGH INTERNATIONAL COLLABORATIVE DIALOGUE: A STUDY OF MALAYSIAN AND AUSTRALIAN PRE-SERVICE TEACHERS - Vegneskumar Maniam; Tay Gerard; Ingrid Harrington; Hayley Trenchard; Susan Bennett (Malaysian Journal of Learning and Instruction)
Purpose - Despite the comprehensive nature of pre-service teacher training programs in Malaysia, the first year of teaching remains a challenging period for novice educators. Effective practices to support the transition to professional life is therefore crucial for teacher retention. This paper presents findings from a prospective study of an ongoing project model developed collaboratively by academics from an Australian public university and a Malaysian public teacher education provider. Together, they facilitated a series of international, dialogue-focused workshops designed to foster collaboration and conversation between Malaysian and Australian pre-service teachers.